The Concept of De-Politicization and Its Consequences - de Nardis, Fabio (PARTECIPAZIONE E CONFLITTO, 2017)
This Issue collects contributions on the theme of the De-Politicization of [representative] pol-itics in the era of neoliberalism. We consider De-politicization as a set of changes in the ways power is exer-cised. These modes downgrade the political nature of decision-making and, through representation, give legitimacy to actors apparently less able to bear witness to the presence of the "political". Politics appears less responsible for the decisions that affect the regulation of society and the impact of their costs and failures on economic and cultural processes. Political choices conditioned by the market acquire the charac-ter of necessity and inevitability. The attempts to legitimize the investigation of public choices through de-liberative arenas governed by non-political parameters, based on information and knowledge, are not ex-ternal to this aspect of de-politicization. A discursive de-politicization determines the convergence of pref-erences into a single, albeit diverse, cognitive construction of reality (frame for public actions). It is no coin-cidence that the prevailing paradigm in the contemporary liberal political economy has been narrated in the form of a "single thought" demonstrating a clear cultural hegemony of the trans-nationalized and financial-ized capitalism. Policies become inevitable responses lacking rational alternatives to the limits of develop-ment set by previous responses, with which contradictions and conflicts had previously been appeased. De-politicization is probably one of the causes of the growing distance between institutional politics and civil society in Western countries and, unavoidably, it determines certain consequences. We think that, on the social side, some of the consequences can be found in the political indifference on the part of citizens (po-litical apathy) and, by contrast, in growing forms of non-institutional social and political participation through the practices of social resilience and resistance; on the political side, we think that one of the con-sequences is the birth, everywhere in Europe, of populist parties and movements that, in their rhetoric, emphasize the intention to give back sovereignty to the people. The aim of this issue is to highlight these phenomena which, also in a critical, provocative way, can contribute to the description of the many aspects of this process through both theoretical and empirical work.